Mekanisme Adaptasi Manusia dalam Lingkungan Ekstrem pada Matra Darat, Laut, dan Udara: Literature Review - Dela Riadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Extreme environments across land, sea, and air domains expose individuals to challenges such as hypoxia, extreme temperatures, pressure changes, isolation, and physical and psychological stress that may affect health and performance. Human adaptation to these conditions involves complex interactions among biological, psychological, social, and spiritual dimensions. However, adaptation mechanisms are often examined separately, requiring a more comprehensive understanding. This study aimed to review human adaptation mechanisms in extreme environments and their implications for military medicine, preventive medicine, occupational health, and operational settings. This study employed a literature review approach to identify, analyze, and synthesize scientific evidence regarding human adaptation mechanisms in extreme environments. The review included original research articles and relevant scientific reports discussing biological, psychological, social, and spiritual aspects among human populations. Only full-text articles in English or Indonesian were included. Biological adaptation includes ventilation regulation, erythropoiesis, thermoregulation, and cardiovascular-respiratory adjustments. Psychological adaptation through coping strategies and emotional regulation reduces stress, while communication, team cohesion, and leadership support social adaptation. Spirituality enhances meaning, hope, and resilience. Human adaptation in extreme environments is a multidimensional process requiring a holistic biopsychosocial-spiritual approach to improve preparedness, health, and resilience among individuals and groups.